Probing local structure of ZnO-modified Pb(Mg1/3Nb2/3)0.9Ti0.1O3 ceramic with synchrotron X-ray absorption spectroscopy technique. Issue 187 (12th February 2018) - Promsawat, M.; Kanchiang, K.; Promsawat, N.; Jiansirisomboon, S.
ABSTRACT: This work aims to study the effects of ZnO modifications on local structures of Pb(Mg1/3 Nb2/3 )0.9 Ti0.1 O3 (PMNT) ceramics. Different contents of ZnO (0, 0.4, 2.0, 4.0 and 11.0 mol%) were added into PMNT ceramics. The local structures of the samples were characterized by synchrotron X-ray absorption spectroscopy (XAS). X-ray absorption near-edge structure (XANES) spectra of both Zn and Ti K-edges were displayed. The Zn K-edge energy values of all samples were in the range of 9660–9666 eV. The Zn ions incorporated in all ceramics were in the form of Zn 2+ . The value of Ti K-edge energy, which was equal to 4979 eV, did not change with ZnO modifications. Comparing the experimental Zn K-edge XANES spectra to the spectra simulated via FTFF program confirmed the substitution of the Zn ions for B-site ions. The intensity and the area under curve of the pre-edge peak of Ti K-edge gradually increased with increasing ZnO content up to 4.0 mol%. This suggested a gradual change in the displacement out from octahedral centers of Ti ions. This could be an evidence of the enhancement in ferroelectric order of ZnO-modified PMNT ceramics.